Communication infrastructures for cloud computing - Mouftah, Hussein T.; Kantarci, Burak, 1981-; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Ave., Hershey, PA, 17033) : IGI Global, 2014)
'This book presents the issues and research directions for a broad range of cloud computing aspects of software, computing, and storage systems, covering topics in communication infrastructures for cloud computing'--Provided by publisher.
Migration path towards cloud-aware core networks / Luis M. Contreras, V{u2A63}tor L{u2BF0}ez, {u23F3}car Gonzez de Dios, Felipe Jim{u296E}ez, Juan Rodruez, Juan Pedro Ferndez-Palacios -- Location and provisioning problems in cloud computing networks / Federico Larumbe, Brunilde Sans{u1BE0}-- The cloud inside the network: a virtualization approach to resource allocation / Jo Soares, Romeu Monteiro, Mcio Melo, Susana Sargento, Jorge Carapinha -- Dimensioning resilient optical grid/cloud networks / Chris Develder, Massimo Tornatore, M. Farhan Habib, Brigitte Jaumard -- Design and implementation of optical cloud networks: promises and challenges / Walid Abdallah, Noureddine Boudriga -- Communication infrastructures in access networks / Syed Ali Haider, M. Yasin Akhtar Raja, Khurram Kazi -- Cloud radio access networks / Jordan Melzer -- Accelerating mobile-cloud computing: a survey / Tolga Soyata, He Ba, Wendi Heinzelman, Minseok Kwon, Jiye Shi -- Performance evaluation of cloud data centers with batch task arrivals / Hamzeh Khazaei, Jelena Mi$1!b0(Bc, Vojislav B. Mi$1!b0(Bc -- Energy-efficient optical interconnects in cloud computing infrastructures / Christoforos Kachris, Ioannis Tomkos -- Energy-efficiency in cloud data centers / Burak Kantarci, Hussein T. Mouftah -- Carrier-grade distributed cloud computing: demands, challenges, designs, and future perspectives / Dapeng Wang, Jinsong Wu -- Energy-efficiency in a cloud computing backbone / Burak Kantarci, Hussein T. Mouftah -- Towards energy efficiency for cloud computing services / Daniele Tafani, Burak Kantarci, Hussein T. Mouftah, Conor McArdle, Liam P. Barry -- Towards energy sustainability in federated and interoperable clouds / Antonio Celesti, Antonio Puliafito, Francesco Tusa, Massimo Villari -- Energy efficient content distribution / Taisir E.H. El-Gorashi, Ahmed Lawey, Xiaowen Dong, Jaafar Elmirghani -- Virtual machine migration in cloud computing environments: benefits, challenges, and approaches / Raouf Boutaba, Qi Zhang, Mohamed Faten Zhani -- Communication aspects of resource management in hybrid clouds / Luiz F. Bittencourt, Edmundo R. M. Madeira, Nelson L. S. da Fonseca -- Scalability and performance management of internet applications in the cloud / Wesam Dawoud, Ibrahim Takouna, Christoph Meinel -- Cloud standards: security and interoperability issues / Fabio Bracci, Antonio Corradi, Luca Foschini.s
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 09/19/2013).
Keywords: Cloud computing; Internetworking (Telecommunication).; Cloud communications; Energy-efficiency.; Identity management; Intrusion detection; Mobile cloud applications; Privacy requirements; Smart applications; Virtual infrastructures